UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN BERDIFERENSIASI PADA KELAS V-A SDN KRANJI II - Ihsan Ridho Muzaffar; Mira Amelia Amri; Waluyo Hadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This classroom action research aims to improve mathematics learning outcomes through the use of differentiated learning models for 26 students in class V-A SDN Kranji II, West Bekasi. Research began in April 2026 in the second semester of the 2024/2025 academic year. The research method used is classroom action research model Kemmis and Mc. Taggart with four stages in each cycle, namely, planning, implementation, observation, and reflection. Data were collected throught observation and tests. Data analysis was carried out by calculating the percentage of test scores at the end of each cycle. The results of research through learning mathematics using differentiated learning models can improve Mathematics learning outcomes. In cycles I and II, mathematics learning outcomes reached a completion percentage of 42,3% and 83,3%. The achievement of teacher action monitoring results in cycles I and II was 65% and 85%, while the achievement of student action monitoring results in cycles I and II was 60% and 88%. The implication of this research is that differentiated learning models can be used as a way to improve Mathematics learning outcomes in class V of elementary school.